The impact of diabetes mellitus on levels of sex hormones and their receptors in tumor tissues in female rats with Guerin’s carcinoma - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; E. I. Surikova; Yu. A. Pogorelova; N. D. Cheryarina; I. M. Kotieva; M. I. Morozova; A. I. Shikhlyarova (Исследования и практика в медицине, 2022)
Purpose of the study. Analysis of the effect of DM on levels of sex hormones and their receptors in tumor and perifocal tissues in outbred white female rats.Materials and methods. Outbred white female rats were divided into 2 groups, 18 rats each: control group – with transplantable Guerin’s carcinoma, main group – with transplantable Guerin’s carcinoma growing in presence of DM. DM was reproduces in animals by the single intraperitoneal alloxan injection (150 mg/kg body weight). Animals were killed after 10 days of the tumor growth. Levels of hormones (estradiol, testosterone, progesterone and prolactin) and their receptors (RЕα, RЕβ, RA and RP4) were measured by ELISA in tumor and perifocal tissues in animals of the control and main groups.Results. Female rats with Guerin’s carcinoma growing in presence of DM showed an increase in glucose in tumor and perifocal tissues by 1.8 times (р < 0.05) and 7.6 times, respectively, compared to the levels in the control group. Levels of E2 were increased, respectively, by 2.4 and 9.5 times; P4 – by 2.1 and 3.0 times; PRL – by 2.7 and 4.4 times. T was increased in perifocal tissues by 2.2 times and was unchanged in tumor tissues. RЕα and RP4 were elevated by 3.9 and 3.0 times, respectively, only in tumor tissues, and RA by 3.9 times only in perifocal tissues. The REα/RЕβ ratio was increased only in the tumor by 3.2 times. The Е2/RЕβ ratio was increased in tumor and perifocal tissues by 2.0 and 9.6 times, respectively. The T/RA ratio was decreased in the tumor and its perifocal area by 1.4 (р < 0.05) and 2.0 times, respectively. The opposite changes were observed in the Е2/RЕα and P4/RP4 ratios: a decrease in the tumor by 1.6 and 1.4 times, respectively (р < 0.05), and an increase in the perifocal area by 9.8 and 2.5 times, respectively.Conclusion. Female rats with Guerin’s carcinoma growing in presence of DM demonstrated local hyperglycemia, changes in the levels of sex steroids and a misbalance in their receptors in tumor and perifocal tissues causing active metastasis and reduced average survival of animals.